# |
ODE |
Mathematica |
Maple |
\[
{}x^{2} y^{\prime } = x^{2} y^{2}+x y+1
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) y^{2}-4 y y^{\prime }-4 x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-4 y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-4 x y y^{\prime }+8 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{2}/{3}}+a
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }+y\right )^{2}+3 x^{5} \left (x y^{\prime }-2 y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \left (y-2 x y^{\prime }\right )^{2} = 2 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}8 {y^{\prime }}^{3}-12 {y^{\prime }}^{2} = 27 y-27 x
\] |
✗ |
✓ |
|
\[
{}\left (y^{\prime }-1\right )^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}y = {y^{\prime }}^{2}-x y^{\prime }+x
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }+y\right )^{2} = y^{\prime } y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y y^{\prime }+{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}3 x {y^{\prime }}^{2}-6 y y^{\prime }+x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {a^{2} {y^{\prime }}^{2}+b^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x -y\right )^{2}+1
\] |
✓ |
✓ |
|
\[
{}x \sin \left (x \right ) y^{\prime }+\left (\sin \left (x \right )-x \cos \left (x \right )\right ) y = \sin \left (x \right ) \cos \left (x \right )-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = y^{n} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}x^{3}-3 x y^{2}+\left (y^{3}-3 x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 x y-4 y^{2}-6 x^{2}+\left (y^{2}-8 x y+\frac {5 x^{2}}{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x y^{2}-x^{2}+\left (3 x^{2} y-6 y^{2}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y-x y^{2} \ln \left (x \right )+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y \,{\mathrm e}^{x^{2}}-x \sin \left (x \right )+{\mathrm e}^{x^{2}} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{2 x -y^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2}+x y^{\prime } = 3 x +y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }-y^{2} = x^{4}
\] |
✓ |
✓ |
|
\[
{}\frac {1}{y^{2}-x y+x^{2}} = \frac {y^{\prime }}{2 y^{2}-x y}
\] |
✓ |
✓ |
|
\[
{}\left (2 x -1\right ) y^{\prime }-2 y = \frac {1-4 x}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x -y+3+\left (3 x +y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\cos \left (\frac {x}{2}+\frac {y}{2}\right ) = \cos \left (\frac {x}{2}-\frac {y}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \left (3 x^{2}-2 x \right )-y \left (6 x -2\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime } x -y^{3} = \frac {x^{4}}{3}
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{\frac {x}{y}}+{\mathrm e}^{\frac {x}{y}} \left (1-\frac {x}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}-x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -y+2+\left (x -y+3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+2 x +2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) \left (y^{2}-y+1\right ) = \left (y-1\right ) \left (x^{2}+x +1\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x -2 x y-y^{2}\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y \cos \left (x \right )+\left (2 y-\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-1 = {\mathrm e}^{x +2 y}
\] |
✓ |
✓ |
|
\[
{}2 x^{5}+4 x^{3} y-2 x y^{2}+\left (y^{2}+2 x^{2} y-x^{4}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{n} y^{\prime } = 2 x y^{\prime }-y
\] |
✓ |
✓ |
|
\[
{}\left (3 x +3 y+a^{2}\right ) y^{\prime } = 4 x +4 y+b^{2}
\] |
✓ |
✓ |
|
\[
{}x -y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2} \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (\ln \left (x \right )\right )-\cos \left (\ln \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {\frac {9 y^{2}-6 y+2}{x^{2}-2 x +5}}
\] |
✓ |
✓ |
|
\[
{}\left (5 x -7 y+1\right ) y^{\prime }+x +y-1 = 0
\] |
✓ |
✓ |
|
\[
{}x +y+1+\left (2 x +2 y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}+2 \left (x^{2}-x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 \left (y+2\right )^{2}}{\left (x +y-1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}4 x^{2} {y^{\prime }}^{2}-y^{2} = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x {y^{\prime }}^{2}-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{4} = 1
\] |
✓ |
✓ |
|
\[
{}x y = y^{\prime } \ln \left (\frac {y^{\prime }}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+3 x = {\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}x^{\prime }-3 x = 3 t^{3}+3 t^{2}+2 t +1
\] |
✓ |
✓ |
|
\[
{}x^{\prime }-x = \cos \left (t \right )-\sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{\prime }+6 x = {\mathrm e}^{-3 t} t
\] |
✓ |
✓ |
|
\[
{}x^{\prime }+x = 2 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{4}}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2} \left (x^{3}+1\right )}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{3} \sin \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {7 x^{2}-1}{7+5 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (2 x \right )^{2} \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = \left (x y^{2}+x \right ) {\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}+{\mathrm e}^{-x}}{y^{2}-{\mathrm e}^{y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}}{1+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sec \left (x \right )^{2}}{y^{3}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (y-y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1-12 x \right ) y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3-2 x}{y}
\] |
✓ |
✓ |
|
\[
{}x +y \,{\mathrm e}^{-x} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}r^{\prime } = \frac {r^{2}}{\theta }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x}{y+x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x}{1+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y^{2}+4 y^{2} x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} {\mathrm e}^{-3 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (1+y^{2}\right ) \tan \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (x^{2}+1\right ) y^{5}}{6}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{2}-{\mathrm e}^{x}}{2 y-11}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y-x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{-x}-{\mathrm e}^{x}}{3+4 y}
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime } = \frac {x}{\sqrt {x^{2}-4}}
\] |
✓ |
✓ |
|
\[
{}\sin \left (2 x \right )+\cos \left (3 y\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}y^{2} \sqrt {-x^{2}+1}\, y^{\prime } = \arcsin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x^{2}+1}{12 y^{2}-12 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x^{2}}{2 y^{2}-6}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y^{2}+x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {6-{\mathrm e}^{x}}{3+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 \cos \left (2 x \right )}{10+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \left (1+x \right ) \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t y \left (4-y\right )}{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t y \left (4-y\right )}{t +1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {a y+b}{c y+d}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = t +{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|